Implementasi Merdeka Belajar Pada Pembelajaran Pai Dalam Meningkatkan Daya Berfikir Kritis Siswa Kelas X Di SMA Ciledug Al Musaddadiyah Garut - Raito, Raito; Dewi, Riska Sintia (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
This research is motivated by the researcher’s attention to the continuity of the learning process at SMA Ciledug Al-Musaddadiyah Garut, which implements the Independent Learning Curriculum (Kurikulum Merdeka Belajar) in the 10th grade. Initial observations indicated that students' critical thinking skills are still low, as evidenced by their difficulties in answering questions from teachers, their inability to express opinions, reluctance to complete school assignments, and lack of enthusiasm for learning. Within the framework of Merdeka Belajar, critical thinking is one of the core elements in shaping the Pancasila Student Profile. Cultivating critical thinking skills is essential for every student as it is crucial for problem-solving and decision-making processes. The objective of this study is to understand the implementation of the Merdeka Belajar curriculum in Islamic Religious Education (PAI) classes and its impact on enhancing the critical thinking abilities of 10th-grade students at SMA Ciledug Al-Musaddadiyah Garut. The research employs a descriptive analytical qualitative method aimed at providing a comprehensive and holistic description and analysis of the implementation of Merdeka Belajar in PAI instruction to improve the critical thinking skills of 10th-grade students at SMA Ciledug Al-Musaddadiyah Garut. Data sources for this research include primary data from observations and interviews with informants from SMA Ciledug Al-Musaddadiyah, and secondary data from reference books, journals, documents, and other relevant archives. Data collection techniques encompass observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The findings of this research demonstrate that the implementation of the Merdeka Belajar curriculum in PAI classes has led to an increase in students' critical thinking skills. This is evidenced by the results of the fifth observation during the learning process, which meet the five critical thinking indicators, showing a notable improvement in students' critical thinking abilities. These findings confirm the positive impact of the Merdeka Belajar approach on students' critical thinking development.  Keywords : Critical Thinking Skills, Implementation, Independent Learning (Merdeka Belajar)